2018
DOI: 10.1108/aeat-01-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Comparing fluid ring and CMG servomechanisms for active control of rigid satellites

Abstract: Purpose This paper aims to describe a novel type of attitude control system (ACS) in different configurations. This servomechanism is compared with control moment gyro (CMG) in significant parameters of performance for ACS of rigid satellite. Design/methodology/approach This new actuator is the fluid containing one or more rings and fluid flow is supplied by pump. The required torque control is obtained by managing fluid angular velocity. The cube-shaped satellite with three rings of fluid in the principle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The authors revealed that the device effectively resisted interference and complete the attitude adjustment task. Akbaritabar [5] studied a novel fluid ring system, it indicates that the feasibility and reliability of the system are proved. Cheng [6] focused on the field distribution about liquid flow and electromagnetic, and the liquid flow transient process in a magnetohydrodynamic fluid ring.…”
Section: Introductionmentioning
confidence: 99%
“…The authors revealed that the device effectively resisted interference and complete the attitude adjustment task. Akbaritabar [5] studied a novel fluid ring system, it indicates that the feasibility and reliability of the system are proved. Cheng [6] focused on the field distribution about liquid flow and electromagnetic, and the liquid flow transient process in a magnetohydrodynamic fluid ring.…”
Section: Introductionmentioning
confidence: 99%
“…A new attitude adjustment device containing several liquid rings was studied by Akbaritabar [7], which used mechanical pumps to drive the liquid. The authors indicated that the device had reliability and some advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexities involved in ADCS design, some efforts have been made to develop simpler algorithms (Akbaritabar et al , 2018; Sun et al , 2018). When the EO-mission requires to design and manufacture a custom ADCS (Tayebi et al , 2017; Hua et al , 2018) then the “design for performance” strategy can be one of the shortest ways to meet the PRs by determining the best values for ADCS DPs (Jia et al , 2019).…”
Section: Introductionmentioning
confidence: 99%